1995
DOI: 10.1103/physrevlett.75.4266
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Coulomb Correlation Gap in a Nonmetallic Semiconductor, Si: B

Abstract: Using electron tunneling, we report the first direct spectroscopic measurement of the Coulomb correlation gap in the density of states N(e) of a nonmetallic doped semiconductor Si:B. In agreement with analytic models, N(e) is found to have a nearly parabolic energy dependence, resulting in a "soft" zero at the Fermi energy, with a gap width =0.75 meV. Resistivity measurements show that this energy governs the observed crossover temperature between noninteracting and correlated hopping transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
117
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 28 publications
15
117
1
Order By: Relevance
“…In the last ten years, several tunneling experiments on weakly insulating samples provided direct evidence for a pseudogap in the density of states around the Fermi level 40,41,42,43,44,45,46,47 . However, such experiments are restricted to the regime relatively close to the metalinsulator transition.…”
Section: B Coulomb Gap and Hopping Transportmentioning
confidence: 99%
“…In the last ten years, several tunneling experiments on weakly insulating samples provided direct evidence for a pseudogap in the density of states around the Fermi level 40,41,42,43,44,45,46,47 . However, such experiments are restricted to the regime relatively close to the metalinsulator transition.…”
Section: B Coulomb Gap and Hopping Transportmentioning
confidence: 99%
“…The experimental trace of the Coulomb interactions between the electrons is the depletion of the single-particle density of states ͑DOS͒ N͑E͒ at the Fermi energy. [2][3][4][5][6][7][8][9] For a dirty three-dimensional system it is found that N͑E͒ϳ ͱ E in the metallic regime, 3,4 whereas N͑E͒ϳE 2 in the insulating regime 2 recently observed in different localized systems, [5][6][7] including magnetically doped materials. 8 Recently, using conductance measurements across the metal-insulator-transition, Lee 9 constructed the phase diagram shown in Fig.…”
mentioning
confidence: 99%
“…7 The presence of the features due to the Coulomb interactions in the conductivity and DOS in disordered systems near the MIT has been well established experimentally. These effects have been mostly observed in experiments performed using the discrete sets of crystalline 8 and amorphous samples 9 with different dopant concentrations close to the critical one.…”
Section: Introductionmentioning
confidence: 99%